Establishment of an oral squamous cell carcinoma cell line expressing vascular endothelial growth factor a and its two receptors - Hanako Araki-Maeda; Mutsuki Kawabe; Yuji Omori; Koji Yamanegi; Kazunari Yoshida; Kyohei Yoshikawa; Kazuki Takaoka; Kazuma Noguchi; Yoshiro Nakano; Hiromitsu Kishimoto (Elsevier, 2022)
Background/purpose: Vascular endothelial growth factor receptor (VEGFR) expression in oral squamous cell carcinoma (OSCC) promotes tumor growth through both autocrine and paracrine signaling. VEGF-positive OSCC cases are associated with a high depth of invasion, increased metastasis, and poor prognosis. In this study we established and then molecularly and functionally analyzed an OSCC cell line that co-expresses VEGF-A, VEGFR-1, and VEGFR-2, termed HCM-SqCC010 cells. Materials and methods: VEGF-A, VEGFR-1, and VEGFR-2 expression in HCM-SqCC010 cells were examined by immunohistochemistry and immunoblotting. Expression and inhibition of VEGF-A, VEGFR-1, and VEGFR-2 in HCM-SqCC010 cells were verified by quantitative real-time PCR. Results: Our analysis of HCM-SqCC010 cells revealed that their proliferation depended on VEGF-A, and selective inhibition of VEGFR-1 or VEGFR-2 resulted in decreased cell growth. Conclusion: We established an OSCC cell line, HCM-SqCC010, that expresses VEGF-A, VEGFR-1, and VEGFR-2. This triple-positive cell line showed no effect from a molecular targeted drug toward VEGF-A, but it did show strong cell growth inhibition in response to a VEGFR inhibitor. Thus, new therapeutic strategies against OSCC should include a VEGFR inhibitor.